The political situation in Syria during the Al-Ahed Al- Fusaily by addressing of Al-Asma newspaper (1919-1920): الأوضاع السياسية في سوريا في العهذ الفيصلي (1919 - 1920) من خلال افتتاحيات صحيفة العاصمة السورية (المجلة العربية للعلوم و نشر الأبحاث, 2017)
The purpose of the study is to analyze the political situation in Syria during the ALahed AL Fusailyby addressing of Al- Asma newspaper (1919-1920), in addition to Prince Faisal's role internally andexternally during the Peace Conference in 1920, And the unity of the States of the Levant, to be the basisfor the launch of a wider Arab unity, and the statement of conspiracy allies on the Arabs, especially Franceand its attempts to occupy Syria, and then efforts by the Syrian Arab state to prevent this, and also brieflydiscussed Prince Faisal talks and meetings and correspondence with the British government from Handand To the governments and political and popular bodies in Syria, Lebanon and Palestine on the otherhand, which revolves around ways to achieve the unity of the countries of the Levant, and then review therole of the Syrian press in the history of modern Arabs in general and Syrian history in particular, whereappeared in the early twentieth century newspapers in Arabic, In the Arab nationalist thought, as a resultof which was persecuted by the Ottoman Empire, and then the French mandate.